Traitor - Pausewang, Gudrun 1928-2020 (Andresen Press, 2004)
When Anna finds an escaped Russian prisoner of war hiding in her grandmother's barn, she knows it's her duty to report him. Instead she provides him with food and clothing and finds him a safer place to hide, hoping that he will try to escape over the Czech border
Keywords: Teenage girls / Fiction; World War, 1939-1945 / Prisoners and prisons / Fiction; World War, 1939-1945 / Fiction; Adolescentes / Romans, nouvelles, etc; Guerre mondiale, 1939-1945 / Prisonniers et prisons / Romans, nouvelles, etc; Prisoners of war; Teenage girls; 1939-1945; Young adult fiction; Fiction; Historical fiction; Young adult works; Jugendbuch